Tethered Pd-complex on solid support: catalyst for acid-free carbonylation reactions - Sarkar, Bibbas R.; Mukhopadhyay, Kausik; Chaudhari, Raghunath V. (Catalysis Communictions, 2007)
{Palladium complex [
Keywords: decomposition; direct H2O2 synthesis; halides; Promoter

Theory-directed designing of an intrinsic-activity-modulated metal-doped copper oxide electrode for nitrate to ammonia synthesis - Tyagi, Nitin Kumar; Mahapatra, Bikash K.; Ghimire, Suvash; Manna, Narugopal; Kumar, Deepak; Kumar, Vijay; Mukhopadhyay, Kausik; Singh, Santosh K. (ACS Applied Energy Materials, 2023)
Synthesis of ammonia via electrochemical reduction ofnitrate isone of the most sustainable routes both for environmental protectionas well as energy saving initiatives. However, this process is limitedto the development of high-performance free-standing catalytic electrodeswith improved selectivity and Faradaic efficiency. Herein, we reporttheory-guided designing and fabrication of free-standing non-noblemetal (Mn, Fe, and Co)-doped copper oxide (CuO) electrodes by usinga simple and scalable electrode preparation method. The density functionaltheory (DFT)-based calculations show that the doped-Co sites in theCu surface facilitate the generation and supply of H+ tothe adsorbed NO3 (-) during the reductionprocess; as a result, the Co-CuO catalyst displays higher selectivitytoward nitrate reduction. The Co-doped Cu electrode (Co-CuO)delivers a higher NH3 yield (5492 mu g cm(-2)) at a reduction potential of -0.91 V vs RHE while maintaininga Faradaic efficiency of >95%. The alloying of Co to the coppermetalnot only facilitates the proton donation to the adsorbed reactant(NO3 (-)) but also tunes the Cu d-center,resulting in the active site modulation responsible for the activationof catalysts.
Keywords: Active sites; ammonia synthesis; electrocatalysis; Faradaic efficiency; High selectivity; metal-doped electrode